Echocardiographic phenotype and prognosis in transthyretin cardiac amyloidosis. (17th January 2020) - Chacko, Liza; Martone, Raffaele; Bandera, Francesco; Lane, Thirusha; Martinez-Naharro, Ana; Boldrini, Michele; Rezk, Tamer; Whelan, Carol; Quarta, Cristina; Rowczenio, Dorota; Gilbertson, Janet A; Wongwarawipat, Tanakal; et al.
Abstract: Aims: Transthyretin amyloidosis cardiomyopathy (ATTR-CM) is an increasingly recognized cause of heart failure. We sought to characterize the structural and functional echocardiographic phenotype across the spectrum of wild-type (wtATTR-CM) and hereditary (hATTR-CM) transthyretin cardiomyopathy and the echocardiographic features predicting prognosis. Methods and results: We studied 1240 patients with ATTR-CM who underwent prospective protocolized evaluations comprising full echocardiographic assessment and survival between 2000 and 2019, comprising 766 with wtATTR-CM and 474 with hATTR-CM, of whom 314 had the V122I variant and 127 the T60A variant. At diagnosis, patients with V122I-hATTR-CM had the most severe degree of systolic and diastolic dysfunction across all echocardiographic parameters and patients with T60AhATTR-CM the least; patients with wtATTR-CM had intermediate features. Stroke volume index, right atrial area index, longitudinal strain, and E / e ' were all independently associated with mortality ( P < 0.05 for all). Severe aortic stenosis (AS) was also independently associated with prognosis, conferring a significantly shorter survival (median survival 22 vs. 53 months, P = 0.001). Conclusion: The three distinct genotypes present with varying degrees of severity. Echocardiography indicates a complex pathophysiology in which both systolic and diastolic function are independently associated with mortality. The presence of severe AS was independently associated with significantly reduced patient survival.